Racial Disparities in Pregnancy-associated Intimate Partner Homicide - Kivisto, Aaron J. (Journal of interpersonal violence, 2022)
Pregnancy-associated femicide accounts for a mortality burden at least as high as any of the leading specific obstetric causes of maternal mortality, and intimate partners are the most common perpetrators of these homicides. This study examined pregnancy-associated and non-pregnancy-associated intimate partner homicide (IPH) victimization among racial/ethnic minority women relative to their non-minority counterparts using several sources of state-level data from 2003 through 2017. Data regarding partner homicide victimization came from the National Violent Death Reporting System, natality data were obtained from the Centers for Disease Control and Prevention?s National Center for Health Statistics, and relevant sociodemographic information was obtained from the U.S. Census Bureau. Findings indicated that pregnancy and racial/ethnic minority status were each associated with increased risk for partner homicide victimization. Although rates of non-pregnancy-associated IPH victimization were similar between Black and White women, significant differences emerged when limited to pregnancy-associated IPH such that Black women evidenced pregnancy-associated IPH rates more than threefold higher than that observed among White and Hispanic women. Relatedly, the largest intraracial discrepancies between pregnant and non-pregnant women emerged among Black women, who experienced pregnancy-associated IPH victimization at a rate 8.1 times greater than their non-pregnant peers. These findings indicate that the racial disparities in IPH victimization in the United States observed in prior research might be driven primarily by the pronounced differences among the pregnant subset of these populations.